THE DEVELOPMENT OF PAPI OPUNG MEDIA TO IMPROVE CHILDREN’S LOGICAL-MATHEMATICS INTELLINGENCE - Tanaya Susilatama Novanti; Intan Prastihastari Wijaya; Hanggara Budi Utomo (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2021)
This research is conducted to develop a product in the form of learning media which is called as Papi Opung to improve logical-mathematics intelligence in early childhood. Moreover, the method used in this research was the research and development (R&D) model from Borg and Gall. Furthermore, we use 6 stages of the existing 10 stages. These stages consist of: (1) potential and problem analysis, (2) literature study, (3) product design, (4) design validation, (5) design revision, and (6) product trial. Data analysis was conducted descriptively and quantitatively. In addition, data were obtained from instrument assessments in the form of validation sheets for media experts and material experts, validation sheets for convenience and attractiveness by teachers group B, observation sheets in small group trials, and observation sheets in field trials. The results of the study show that papi opung media are relevant, feasible, and valid for increasing logical-mathematics intelligence in early childhood.Keywords: Papi Opung Media; Logical-Mathematics; Early Childhood. AbstrakPenelitian ini dilakukan untuk mengembangkan suatu produk berupa media pembelajaran yang disebut Papi Opung untuk meningkatkan kecerdasan logika-matematika pada anak usia dini. Selain itu, metode yang digunakan dalam penelitian ini adalah model penelitian dan pengembangan (R&D) dari Borg and Gall. Selanjutnya kami menggunakan 6 tahapan dari 10 tahapan yang ada. Tahapan tersebut terdiri dari: (1) analisis potensi dan masalah, (2) studi literatur, (3) desain produk, (4) validasi desain, (5) revisi desain, dan (6) uji coba produk. Analisis data dilakukan secara deskriptif kuantitatif. Selain itu, data diperoleh dari penilaian instrumen berupa lembar validasi ahli media dan ahli materi, lembar validasi kemudahan dan daya tarik guru kelompok B, lembar observasi uji coba kelompok kecil dan lembar observasi uji coba lapangan. Hasil penelitian menunjukkan bahwa media papi opung relevan, layak, dan valid untuk meningkatkan kecerdasan logika-matematika pada anak usia dini.Kata Kunci: Media Papi Opung; Logika-Matematika; Anak Usia Dini.